Screening for Antimicrobial Activities and Enzymatic Activities Production of Some Actinomycetes spp. Isolated from different Soil Samples from Hilla Province (British Journal of Multidisciplinary and Advanced Studies, 2023)
One hundered and fifty soil samples were collected from different city of Babylon /Iraq. Thirty-three Actinomycetes isolates were obtained, purified and identified according to morphological properties and biochemical tests. All isolates were tested for their antimicrobial activities and screened for production of some important enzymes such as amylase, catalase, protease, cellulase and lipase. The results obtained that 13 isolated have such potential and all 13 isolates have amylase activity. The most active isolates in production of study enzymes were KO-AG18, HI-SA24 and KO-RS27. Most 13 Actinomycetes isolates were showed antimicrobial against some Gram -positive bacteria (Staphylococcus albus, Staphylococcus aureus and Streptococcus pyogenes) and Gram- negative (Klebsella pneumoniae, Escherichia coli, , Serratia marcescens, Pseudomonas aeruginosa and Aeromonas hydrophila due to inhibition zone diameter (mm) ranged from 4-37 against gram negative and from 6- 37 against gram positive bacteria.